2017
DOI: 10.3390/nu9020123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Folic Acid Supplementation during Pregnancy and Childhood Allergic Disease Outcomes: A Question of Timing?

Abstract: Abstract:Since the early 1990s, maternal folic acid supplementation has been recommended prior to and during the first trimester of pregnancy, to reduce the risk of infant neural tube defects. In addition, many countries have also implemented the folic acid fortification of staple foods, in order to promote sufficient intakes amongst women of a childbearing age, based on concerns surrounding variable dietary and supplementation practices. As many women continue to take folic acid supplements beyond the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 81 publications
(102 reference statements)
4
30
0
1
Order By: Relevance
“…It has been clearly demonstrated that low maternal folate intake during the periconceptional period increases the risk for neural tube defect (e.g., spina bifida, anencephaly) and perhaps for other congenital anomalies (e.g., congenital heart defects, oral cleft lip and plate) and adverse outcomes [17]. In our study, for instance, we reported higher proportions of SGA and LGA births among women with inadequate folate intake compared with those who met dietary recommendation.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…It has been clearly demonstrated that low maternal folate intake during the periconceptional period increases the risk for neural tube defect (e.g., spina bifida, anencephaly) and perhaps for other congenital anomalies (e.g., congenital heart defects, oral cleft lip and plate) and adverse outcomes [17]. In our study, for instance, we reported higher proportions of SGA and LGA births among women with inadequate folate intake compared with those who met dietary recommendation.…”
Section: Discussionsupporting
confidence: 49%
“…Beyond folate intake, supplementation of folic acid during the periconceptional period represents one of the best strategies to tackle pregnancy adverse outcomes, as suggested by the WHO in 2006 [17]. However, the prevalence of folic acid supplementation remains often inadequate in several countries [20,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is likely to be multifactorial, there has been interest in the role of specific nutrients, such as the changes in vitamin D, folate and n-3 PUFA status based on the documented immunomodulatory properties of these nutrients, as discussed in detail elsewhere [59,60]. Although there are no specific recommendations for allergy prevention with regard to specific nutrients at this stage, there is the need for a better understanding of nutritional programming of immune health, nutritional epigenetics and other biological processes sensitive to nutritional ex- posures in early life.…”
Section: Australiamentioning
confidence: 99%
“…Such disappointing findings have not prevented omega‐3 fatty acids from finding their way into many pregnancy multivitamins on the premise of improving fetal neurodevelopment. Finally, high prenatal folic acid exposure, particularly beyond the first trimester, has been associated with an increased risk of childhood atopic disease …”
mentioning
confidence: 99%